Pengembangan Perangkat Pembelajaran Matematika dengan Metode Problem Solving Berbantuan Ms. Excel pada Materi Solusi Sistem Persamaan Linear - Aminudin, Mohamad (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The research aimed at 1) producing teaching documents of mathematics byusing ms.excel based problem solving method on the linear equivalencematerial; 2) describing the prcticality of the document usage; 3) measuring theeffectivenessof ms. Excel based problem solving method. This research usedthe plomp development model consisting of investigation phase, realizationphase, test phase, evaluation and revision, and implementation phase. Theteaching documents developed were syllabus, lesson plan and module had beenvalidated and examined. The subjects of research were the 6th semesterstudents of mathematics education of Teachers Training and Education Facultyof Pancasakti University. By using cluster sampling there were 2 classes out of4 classes used as the participants. The first class, VIB was used as theexperiment class and the other, VID, was used as the control class. The datawere collected through the use of documentation, observation, questionairesand test and then they were analyzed by using T-one sample. The resultsshowed that the teaching documents developed had fullfilled the criteria ofgood documents as it was reflected by (1) the validation of experts, achievingthe score of 3,5 which means the teaching documents were valid, (2) theobservation results of lectures’abilities in managing the class got the score 3,04and the student’s responser were high, and 3) the effectiveness of the teachingand learning shown by the average test score on problem solving 72,8, a higherscore than the minimum score 70.Key Word :document development, problem solving, solution of linearequivalence system.